Possibility of artocarpus heterophyllus latex as an alternative source for natural rubber. (October 2019) - Bhadra, Sambhu; Mohan, Nitin; Parikh, Gaurang; Nair, Sujith
Abstract: Natural rubber (NR) has much application in rubber product manufacturing industries, which cannot be replaced by synthetic rubber. At present, Hevea rubber tree is the only economical and commercially viable source of NR. Therefore, the objective of the present research was to find alternative source of NR. NR mainly comprise of cis -1, 4 polyisoprene. Artocarpus heterophyllus latex (jackfruit latex) was collected and analyzed to investigate if it can be considered as alternative source of NR. It was found from FTIR, 1 H NMR and GC-MS study that jackfruit latex contains both cis -1, 4 polyisoprene and trans - 1, 4 polyisoprene along with few other chemical constituents. However, molecular weight of jackfruit latex is significantly lower than the NR. Because of low molecular weight polymer and presence of several other chemical constituents as impurity, jackfruit latex does not impart significant mechanical properties in vulcanized rubber compound, but it provides additional wet skid resistance (WSR) and aid in better dispersion of carbon black in rubber compound. Therefore, jackfruit latex cannot be used to replace NR, but can be used as low molecular weight natural resin, especially to improve dispersion of carbon black in rubber compound and to enhance WSR for tire. Highlights: Natural rubber (NR), having many important applications, cannot be replaced with synthetic rubber. NR is obtained only from Hevea brasiliensis tree. Therefore, there is a need to find alternative sources of NR. In this study, Artocarpus heterophyllus latex (jackfruit latex) was investigated to check if it can be used as an alternative source for NR. Jackfruit latex imparts additional wet skid resistance (WSR) and aid in better dispersion of carbon black in rubber compound.